2022
DOI: 10.1111/pim.12910
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical immune response in leishmaniasis: The role of toll‐like receptors in disease progression

Abstract: Toll-like receptors (TLRs), members of pattern recognition receptors, are expressed on many cells of the innate immune system, and their engagements with antigens regulate specific immune responses. TLRs signalling influences species-specific immune responses during Leishmania infection; thus, TLRs play a decisive role towards elimination or exacerbation of Leishmania infection. To date, there is no single therapeutic or prophylactic approach that is fully effective against leishmaniasis. An in-depth understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 101 publications
0
3
0
1
Order By: Relevance
“…Failure to activate the TLR2 downstream pathway can affect DC activation, influencing the development of the T-cell immune response against L. infantum infection [ 69 , 70 ]. On the other hand, in vitro L. amazonensis infectivity was much higher in the BMDM of TLR2 −/− C57BL/6 mice when compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to activate the TLR2 downstream pathway can affect DC activation, influencing the development of the T-cell immune response against L. infantum infection [ 69 , 70 ]. On the other hand, in vitro L. amazonensis infectivity was much higher in the BMDM of TLR2 −/− C57BL/6 mice when compared to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the detection of L. donovani CpG DNA by TLR-9 [54] can trigger a Th1-mediated immune response [55], and the anti-leishmanial effect of miltefosine in infected THP1 cells or peripheral blood mononuclear cells from VL patients has also been linked to proinflammatory responses driven by TLR-9, demonstrating that TLR-9 is necessary for parasite control [56]. Therefore, it is reasonable to suggest that the upregulation of TLR-9 mRNA expression and the consequent activation of downstream signaling in LdCen −/− infected DCs could be essential in the proinflammatory response triggered by the vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…They are mostly expressed by antigen-presenting cells (APCs), and their engagement with pathogen associated molecular patterns ( PAMPs ) on the Leishmania surface leads to the activation of the microbicidal responses of phagocytes, such as the production of superoxide and nitric oxide [ 41 ]. TLR 2 is the most relevant to Leishmania infection and is centrally responsible for the recognition of lipophosphoglycan (LPG), the greatest expressed surface molecule in Leishmania parasites [ 42 , 43 ]. TLR 2 is involved in the resistance against L. ( L. ) infantum -infection since it promotes the development of Th1 and Th17 protective immune responses, and also the activation of dendritic cells and neutrophils, which trigger the TNF-α and nitric oxide production, amplifying the immunity against L. ( L. ) infantum (and probably L. ( L. ) chagasi as well) [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%